Serial olfactory testing for the diagnosis of prodromal Parkinson's disease in the PARS study - Vaswani, Pavan A.; Morley, James F.; Jennings, Danna; Siderowf, Andrew; Marek, Kenneth; Jennings, Danna; Marek, Ken; Seibyl, John; Siderowf, Andrew; Stern, Matthew; Russell, David; Sethi, Kapil; et al. (Parkinsonism & related disorders, 2022)
The Parkinson Associated Risk Syndrome (PARS) study was designed to evaluate whether screening with olfactory testing and dopamine transporter (DAT) imaging could identify participants at risk for developing Parkinson's disease (PD). Hyposmia on a single test has been associated with increased risk of PD, but, taken alone, lacks specificity. We evaluated whether repeating olfactory testing improves the diagnostic characteristics of this screening approach. Participants completed up to 10 years of clinical and imaging evaluations in the PARS cohort. Olfaction was assessed with the University of Pennsylvania Smell Identification Test at baseline and on average 1.4 years later. Multiple logistic regression and Cox proportional hazards regression were used to estimate the hazard of development of clinical PD or abnormal DAT imaging. Of 186 participants who were initially hyposmic, 28% reverted to normosmia on repeat testing (reverters). No initially normosmic subjects and only 2% of reverters developed DAT imaging progression or clinical PD, compared to 29% of subjects with persistent hyposmia who developed abnormal DAT and 20% who developed clinical PD. The relative risk of clinical conversion to PD was 8.3 (95% CI:0.92–75.2, p = 0.06) and of abnormal DAT scan was 12.5 (2.4–156.2, p = 0.005) for persistent hyposmia, compared to reversion. Persistent hyposmia on serial olfactory testing significantly increases the risk of developing clinical PD and abnormal DAT imaging, compared to hyposmia on a single test. Repeat olfactory testing may be an efficient and cost-effective strategy to improve identification of at-risk patients for early diagnosis and disease modification studies. •Hyposmia, impaired sense of smell, is associated with increased risk of Parkinson's disease.•By itself, smell testing is sensitive, but lacks specificity.•Repeating smell testing is a simple and cost-effective way to improve this screening tool.